The Increased Ratio of Blood CD56bright NK to CD56dim NK Is a Distinguishing Feature of Primary Sjögren's Syndrome. (9th July 2020) - Ming, Bingxia; Wu, Tong; Cai, Shaozhe; Hu, Peng; Tang, Jungen; Zheng, Fang; Ye, Cong; Dong, Lingli
Abstract : Objective . The aim of this study was to characterize the subsets of circulating CD56 + NK cells in pSS patients and their potential value in the diagnosis and/or prediction of prognosis in patients with pSS. Methods . We included 52 pSS patients fulfilling the 2002 AECG criteria or 2012 ACR criteria and 20 age- and gender-matched healthy volunteers. The frequency and absolute number of NK cells and CD56 NK cell subsets in peripheral blood samples were detected by flow cytometry. Other laboratory parameters such as the IgG level and complement protein levels were extracted from the clinical system. Results . Both the frequency and the absolute number of peripheral blood NK cells were reduced in pSS patients compared to healthy controls. The proportion of CD56 bright NK cell subset was increased, and the proportion of CD56 dim NK cell subset was decreased among NK cells, resulting in the ratio of CD56 bright NK to CD56 dim NK which was significantly elevated in pSS patients. ROC analysis indicated that the AUC of CD56 bright NK/CD56 dim NK ratio was 0.838, and the best diagnostic cut-off point was 0.0487 for pSS patients. Furthermore, this CD56 bright NK/CD56 dim NK ratio was positively correlated with the IgG level and negatively correlated with the complement protein C3 and C4 levels. More importantly, the CD56 bright /CD56 dim NK ratio was either slightly increased or not changed in other autoimmune diseases such as SLE and IgG4-related disease. Conclusion . Our findings suggest that the ratio of blood CD56 bright NK to CD56 dim NK might have a diagnostic value relatively specific for pSS.